2006
DOI: 10.1515/znc-2006-11-1203
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotease and Antimetastatic Activity of Ursolic Acid Isolated from Salvia officinalis

Abstract: Proteases play a regulatory role in a variety of pathologies including cancer, pancreatitis, thromboembolic disorders, viral infections and many others. One of the possible strategies how to combat with these pathologies seems to be the use of low molecular inhibitors. Natural products were evaluated in the in vitro antiprotease assay on serine proteases (trypsin, thrombin and urokinase) and on the cysteine protease cathepsin B. We found interesting results for -ursolic acid isolated from Salvia officinalis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Thus, in this study, we have shown that LEJ most likely exerts its anti-metastatic effects via ursolic acid and 2α-hydroxyursolic acid. Many reports have noted that ursolic acid has potent antimetastatic activity (Jedinák et al, 2006;Raphael and Kuttan, 2008). However, as far as we know, the MMP-2 and MMP-9 inhibitory activity of 2α-hydroxyursolic acid has not yet been reported.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, in this study, we have shown that LEJ most likely exerts its anti-metastatic effects via ursolic acid and 2α-hydroxyursolic acid. Many reports have noted that ursolic acid has potent antimetastatic activity (Jedinák et al, 2006;Raphael and Kuttan, 2008). However, as far as we know, the MMP-2 and MMP-9 inhibitory activity of 2α-hydroxyursolic acid has not yet been reported.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, new therapeutic drugs with reduced side-effects and better bioavailability are needed. Triterpenoids are structurally diverse organic compounds with promising anticancer and antimetastatic activity (25,26). The medicinal mushroom G. lucidum is a rich source of triterpenes with anticancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, immunohistochemistry revealed that UA also regulates the metastatic biomarker ICAM-1 [37]. Tumor invasion linked to proteases, such as urokinase and cathepsin B, is also suppressed by UA [38]. A study of C6 glioma cells found that UA inhibits the expression of matrix metalloproteases (MMPs) by regulating NF-κB via the up-regulation of IκB inhibitors [39].…”
Section: Anti-metastasismentioning
confidence: 99%